Trichoderma koningiopsis (Hypocreaceae) has the smallest mitogenome of the genus Trichoderma - Castrillo, María Lorena; Bich, Gustavo Ángel; Amerio, Natalia Soledad; Barengo, Marcela Paola; Zapata, Pedro Darío; Saparrat, Mario Carlos Nazareno; Villalba, Laura Lidia (Frontiers in Microbiology, 2023)
Introduction Fungal mitogenomes exhibit remarkable variation in conformation, size, gene content, arrangement and expression, including their intergenic spacers and introns. Methods The complete mitochondrial genome sequence of the mycoparasitic fungus Trichoderma koningiopsis was determined using the Illumina next-generation sequencing technology. We used data from our recent Illumina NGS-based project of T. koningiopsis genome sequencing to study its mitochondrial genome. The mitogenome was assembled, annotated, and compared with other fungal mitogenomes. Results T. koningiopsis strain POS7 mitogenome is a circular molecule of 27,560 bp long with a GC content of 27.80%. It harbors the whole complement of the 14 conserved mitochondrial protein-coding genes (PCG) such as atp6, atp8, atp9, cox1, cox2, cox3, cob, nad1, nad2, nad3, nad4, nad4L, nad5, and nad6, also found in the same gene order to other Hypocreales. The mitogenome also contains 26 transfer RNA genes (tRNAs), 5 of them with more than one copy. Other genes also present in the assembled mitochondrial genome are a small rRNA subunit and a large rRNA subunit containing ribosomal protein S3 gene. Despite the small genome size, two introns were detected in the T. koningiopsis POS7 mitogenome, one of them in cox3 gene and the other in rnl gene, accounting 7.34% of this mitogenome with a total size of 2,024 bp. A phylogenetic analysis was done using the 14 PCGs genes of T. koningiopsis strain POS7 mitogenome to compare them with those from other fungi of the Subphyla Pezizomycotina and Saccharomycotina. T. koningiopsis strain POS7 was clustered together with other representatives of Trichoderma lineage, within the Hypocreales group, which is also supported by previous phylogenetic studies based on nuclear markers. Discussion The mitochondrial genome of T. koningiopsis POS7 will allow further investigations into the taxonomy, phylogenetics, conservation genetics, and evolutionary biology of this important genus as well as other closely related species.